If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2(3 + -1x) = 7x + 5 6x + (3 * 2 + -1x * 2) = 7x + 5 6x + (6 + -2x) = 7x + 5 Reorder the terms: 6 + 6x + -2x = 7x + 5 Combine like terms: 6x + -2x = 4x 6 + 4x = 7x + 5 Reorder the terms: 6 + 4x = 5 + 7x Solving 6 + 4x = 5 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + 4x + -7x = 5 + 7x + -7x Combine like terms: 4x + -7x = -3x 6 + -3x = 5 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -3x = 5 + 0 6 + -3x = 5 Add '-6' to each side of the equation. 6 + -6 + -3x = 5 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = 5 + -6 -3x = 5 + -6 Combine like terms: 5 + -6 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 6x+9y=360 | | 1/3×5/2 | | 2(13/5) | | 1/3=5/2x-8/3 | | 6(t-6)+8t=7(2t+3)-8 | | 4/5y=6 | | 180x+96y=60 | | n^2(-2n^2+7n-4)= | | 30=16=1/5x | | -18+7y=-12+4y | | 1-(7n+9)= | | 2x+3x-5=8 | | 4m^2+4m-1=0 | | 24vw^5x^3+30v^8w^9=0 | | 7[x-3(2y-7x)]= | | 12x+6=0+3x | | (x-0.5)(x-0.5)-1.561=0 | | a(2-a)= | | y-9(-5.5)=3 | | 10/280 | | 2-4=r | | 6+3(3.4)= | | -2(x+5)+4=3(x+4)+1 | | -1/6y-(y-4/7)=1/42(y-8) | | 3x*(4/9) | | 20*1/2= | | -(x-4)=3x-20 | | -4.8+7(-1-3(25))=3(-1-7(25)) | | X[n]=2u[-n] | | -4.8+7(-1.2-3(36))=3(-1.2-7(36)) | | 5x(4x+6)=-4 | | -4.8+7(1.2-3(36))=3(1.2-7(36)) |